The speed of alpha-band oscillations predicts the temporal resolution of visual perception - Samaha, Jason (Curr Biol, 2015)
Evidence suggests that scalp-recorded occipital alpha-band (8-13 Hz) oscillations reflect phasic information transfer in thalamocortical neurons projecting from LGN to visual cortex [1–5]. In animals, the phase of ongoing alpha oscillations has been show to modulate stimulus discrimination and neuronal spiking [6]. Human research has shown that alpha phase predicts visual perception of near-threshold stimuli [7–11] and subsequent neural activity [12–14], and that the frequency of these oscillations predicts reaction times [15], as well as the maximum temporal interval necessary for perceived simultaneity [16]. These phasic effects have lead to the hypothesis that conscious perception occurs in discrete temporal windows, clocked by the frequency of alpha oscillations [17–21]. Under this hypothesis, variation in the frequency of occipital alpha oscillations should predict variation in the temporal resolution of visual perception. Specifically, when two stimuli fall within the same alpha cycle they may be perceived as a single stimulus, resulting in perception with lower temporal resolution when alpha frequency is lower. We tested this by assessing the relationship between two-flash fusion thresholds (a measure of the temporal resolution of visual perception), and the frequency of eyes-closed and task-related alpha rhythms. We found, both between- and within-subjects, that faster alpha frequencies predicted more accurate flash discrimination, providing novel evidence linking alpha frequency to the temporal resolution of perception.